The Association Between Mobile Dating Apps Use, Sexually Transmitted Infections and Risky Sexual Behaviour in Ontario University Students - Miller, Alanna (My University, 2020)
Over the last decade, the incidence rates of many sexually transmitted infections (STI) have been on the rise, especially amongst young adults. Popular Canadian media outlets have speculated that the reason behind these increases is the use of mobile dating applications which foster romantic and sexual connections. This cross-sectional study assesses whether students who use mobile dating apps are more or less likely to have been diagnosed with an STI in the previous 12 months and engage in risky sexual behaviour, compared to students who did not use mobile dating apps in the previous 12 months. An anonymous online questionnaire was used to collect data from 965 study participants currently enrolled at an Ontario university. The survey required participants to self-report STI testing behaviour and diagnoses, as well as sexual behaviours, including number of sexual partners, relationship type, condom use, substance use and sex work. I found that Ontario university students who used dating apps in the previous 12 months were more likely to have a greater number of sexual partners in the previous year (p<0.05), have multiple concurrent sexual partners (OR=10.72, 95% CI: 6.10-18.84), frequently use alcohol (OR=3.94, 95% CI:2.17-7.14) and cannabis (OR=3.36, 95% CI:1.45-7.78) in combination with sexual activity, and were more likely to have been tested for STIs in the previous 12 months (OR=2.25, 95% CI: 1.73-2.94) compared to non-dating app users. However, mobile dating app users were not more likely to have been diagnosed with an STI in the previous 12 months compared to non-dating app users.
Dating Apps, Sexually Transmitted Infections and Risky Sexual Behaviour
Keywords: sexual health; public health; sexually transmitted infection; sexual behaviour